Terrorism: understanding the global threat - Whittaker, David J. (London, 2002)
What is terrorism and where does it come from? Who are the people who perpetrate terror? What are their motives? 11th September 2001 was the defining moment not only of 2001, but of the new millenium. Terrorism is now everybody's major and constant fear. This easy-to-read, concise account of terrorism provides the essential global guide to understanding what the threat is and exactly where it comes from. Without this knowledge, argues David Whittaker, there can be no way forward in prevention and control. The book looks in particular at how terrorism has shaped and been shaped by the past half century, the driving forces behind it, the methods, the psychology and the money. Arranged in 10 clearly defined thematic sections, and presented in the form of newspaper columns, this unbiased and unpartisan account provides information and reassurance.
Keywords: Terrorism